Pengembangan Digital Worksheet Materi Transformasi Geometri untuk Meningkatkan Pemahaman Konsep Matematis Siswa SMP - Wijayanti, Titin; Hartono, Yusuf; Hiltrimartin, Cecil (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to develop a digital worksheet assisted by wizer.me on geometric transformation material, particularly translation and reflection, as an alternative learning medium that is more interactive for junior high school students. The development was carried out using the Plomp model through the preliminary, design, reconstruction, testing, evaluation and revision, and implementation phases. The results of validation by experts showed that the developed product had a very good level of validity in terms of content, construct, ICT, and language, with an average score above 87%. Meanwhile, the practicality test in a small group also showed a positive response from students with a score of more than 82%, indicating that the digital worksheet was practical to use in the learning process. The effectiveness of the media was tested by giving pretest and posttest questions to 28 students. There was a significant increase in learning outcome, with the average pretest and posttest scores increasing by 40.58 with N-gain value of 0.59, which is in the moderate category and is reinforced by the results of the Paired Sample t-Test, which shows a difference in scores before and after learning. Therefore, it can be concluded that digital worksheets assisted by wizer.me are quite effective in supporting students’ understanding of geometric transformation material, making them suitable for use as an innovative learning medium in the classroom.